CURRENT PROBLEMS OF EMPLOYMENT OF SOCIALLY VULNERABLE SEGMENTS OF THE POPULATION: THEORETICAL AND LEGAL ASPECT - Stadnichenko, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to consider the features of employment of persons with disabilities and persons with reduced working capacity. It is emphasized that the employment of these categories of citizens is an important aspect of their socio-economic integration. The article defines the basic rights of persons with disabilities and persons with limited working capacity in the labor sphere, as well as the features of employment of this category of citizens. The article also considers measures that can contribute to increasing the level of employment of persons with disabilities and persons with reduced working capacity. To investigate the current state of social reforms and their impact on social security in Ukraine, in particular, deserving attention to European social standards as potential guidelines for the latest model of sources of social security law. Research methods: the study is based on the analysis of modern research in the field of social reforms and uses methods of evaluation and comparative analysis. European experience and practice are studied as key components for understanding the optimal ways to improve social protection. Results: the study revealed the need for further study and implementation of European social standards to address the problems of efficiency, accessibility and inclusiveness of the Ukrainian social protection system. Analysis of current trends in social reforms provides important guidelines for further improvement. Discussion: the purpose of the discussion is to identify specific measures to improve social protection in Ukraine based on European standards. The need for deeper study and adaptation of best practices to increase the efficiency and inclusiveness of the system is noted. This article is distinguished by its focus on the practical application of European experience in the context of Ukrainian social reforms, creating a basis for further discussions and improving the social security sector in Ukraine. The conclusion of the article is that the employment of persons with disabilities and persons with reduced working capacity is an important task of society. To solve it, it is necessary to ensure compliance with the rights of this category of citizens in the labor sphere, as well as to develop and implement effective measures for their employment.